Freely Tunable Dual-Passband Microwave Photonic Filter Based on Phase-to-Intensity Modulation Conversion by Stimulated Brillouin Scattering - Zhen Zeng; Zhiyao Zhang; Zhengkai Li; Jun Yuan; Shangjian Zhang; Yali Zhang; Zhengping Zhang; Yong Liu (IEEE Photonics Journal, 2019)
An approach to achieving a highly selective and stable microwave photonic filter (MPF) with two passbands independently tunable is presented. The dual-passband MPF is realized based on phase-to-intensity modulation conversion by stimulated Brillouin scattering. In the proposed scheme, a freely tunable two-tone pump is generated by passing the optical carrier through two cascaded dual-parallel Mach-Zehnder modulators (DPMZMs), with one acting as a frequency shifter with assistance of an electrical 90° hybrid and the other one working at carrier-suppressed double-sideband modulation mode to generate two-tone pump. The two passband locations of the MPF can be freely set by adjusting the frequencies of the two single-tone signals applied to the two DPMZMs. In the experiment, a dual-passband MPF with flexible passband tunability and shape-invariant tuning is demonstrated in the frequency range of 0–9.644 GHz, where the out-of-band rejection ratio and the 3-dB bandwidth of the passbands are measured to be larger than 25 dB and smaller than 55 MHz, respectively. The proposed MPF scheme also has the ability to tailor the shape and the width of the two passbands, which is a promising solution to achieve a freely programable dual-passband MPF.